Natural sources and encapsulating materials for probiotics delivery systems: Recent applications and challenges in functional food development - Singh, Shubhi; Gupta, Rishibha; Chawla, Sonam; Gauba, Pammi; Singh, Manisha; Tiwari, Raj Kumar; Upadhyay, Shuchi; Sharma, Shalini; Chanda, Silpi; Gaur, Smriti (Frontiers in Nutrition, 2022)
Probiotics are known as the live microorganisms which upon adequate administration elicit a health beneficial response inside the host by decreasing the luminal pH, eliminating the pathogenic bacteria in the gut as well as producing short chain fatty acids (SCFA). With advancements in research; probiotics have been explored as potential ingredients in foods. However, their use and applications in food industry have been limited due to restrictions of maintaining the viability of probiotic cells and targeting the successful delivery to gut. Encapsulation techniques have significant influence on increasing the viability rates of probiotic cells with the successful delivery of cells to the target site. Moreover, encapsulating techniques also prevent the live cells from harsh physiological conditions of gut. This review discusses several encapsulating techniques as well as materials derived from natural sources and nutraceutical compounds. In addition to this, this paper also comprehensively discusses the factors affecting the probiotics viability and evaluation of successful release and survival of probiotics under simulated gastric, intestinal conditions as well as bile, acid tolerant conditions. Lastly applications and challenges of using encapsulated bacteria in food industry for the development of novel functional foods have also been discussed in detail too. Future studies must include investigating the use of encapsulated bacterial formulations in in-vivo models for effective health beneficial properties as well as exploring the mechanisms behind the successful release of these formulations in gut, hence helping us to understand the encapsulation of probiotic cells in a meticulous manner.